2014
DOI: 10.1371/journal.pone.0108071
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Localization and Transduction by Adenoviral Vectors Are Serotype-Dependent and Can Be Modified by Inclusion of RGD Fiber Modifications

Abstract: PurposeTo evaluate localization and transgene expression from adenoviral vector of serotypes 5, 35, and 28, ± an RGD motif in the fiber following intravitreal or subretinal administration.MethodsOcular transduction by adenoviral vector serotypes ± RGD was studied in the eyes of mice receiving an intravitreous or subretinal injection. Each serotype expressed a CMV-GFP expression cassette and histological sections of eyes were examined. Transgene expression levels were examined using luciferase (Luc) regulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…By quantifying the number of corrected TM cells in vivo, we found an estimated transduction efficiency of at least ∼60-70% using Ad5-cas9 and/or Ad5-crMYOC. Of note, we also found Cas9 expression in the cornea endothelium and parts of the iris and ciliary body, similar to previous studies with adenovirus transduction (36)(37)(38). Western blot analysis data also showed reductions in myocilin, BiP, Calnexin, PDI, ATF4, and CHOP levels, confirming our ICC data indicating gRNA targeting in Tg-MYOC Y437H mice (Fig.…”
Section: Crispr-cas9 Lowers Iop and Prevents Further Glaucomatous Damagesupporting
confidence: 91%
“…By quantifying the number of corrected TM cells in vivo, we found an estimated transduction efficiency of at least ∼60-70% using Ad5-cas9 and/or Ad5-crMYOC. Of note, we also found Cas9 expression in the cornea endothelium and parts of the iris and ciliary body, similar to previous studies with adenovirus transduction (36)(37)(38). Western blot analysis data also showed reductions in myocilin, BiP, Calnexin, PDI, ATF4, and CHOP levels, confirming our ICC data indicating gRNA targeting in Tg-MYOC Y437H mice (Fig.…”
Section: Crispr-cas9 Lowers Iop and Prevents Further Glaucomatous Damagesupporting
confidence: 91%
“…AdV requires handling at biosafety level (BSL) 2. The nonspecific transduction can be made more specific by transcriptional targeting (Gonzalez et al, 2004) or choosing select sub-serotypes (Ueyama et al, 2014). …”
Section: Established Methods Of Ocular Gene Therapymentioning
confidence: 99%
“…A TM preferential promoter is the matrix Gla protein promoter (Gonzalez et al, 2004) or chitinase 3-like 1 promoter (Liton et al, 2005). Ueyama et al found that an unmodified Ad35 serotype preferentially transduces TM cells (Ueyama et al, 2014). …”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Several different viral vectors have been used to transduce the TM including: Adenovirus serotypes 5 (Ad5) (Hoffman et al , 1997; Millar et al , 2008), 28 or 35 (Ueyama et al , 2014), self-complementary Adeno-Associated Virus (scAAV) (Buie et al , 2010), Herpes Simplex Virus (HSV) (Spencer et al , 2000), HIV pseudotyped with VEEV-G or VSV-G (Lipinski et al , 2014), and Equine infectious anemia virus (EIAV) pseudotyped with VSV-G (Balaggan et al , 2006). …”
Section: Introductionmentioning
confidence: 99%